Color Coding and Thematic Environmental Graphic Design in Hermina Children’s Hospital - Dwiputri, Asri; Swasty, Wirania (Journal of Visual Art and Design, 2019)
Hospitalization has a psychological impact on pediatric patients. A hospital is a complex environment, so wayfinding information needs to be provided by environmental graphics inside the building. It is necessary to design informative, communicative and educative environmental graphic design media that use color coding to support child development. The research problem was to create an environmental graphic design (EGD) for a children’s hospital that is communicative, attractive and educative and to investigate the role of color coding in the design. A case study was conducted at Hermina Hospital Depok, which consisted of literature study, observation, interviews and questionnaires. Color coding was used as a strategy to differentiate areas and to provide an understanding of the layout of the hospital complex. The purpose of this study was to design an effective EGD for a hospital as a means of information and communication to the visitors, especially children. Another aim was to apply color coding to a complex area.